Methylsulfonyl Zn phthalocyanine: A polyvalent and powerful hydrophobic photosensitizer with a wide spectrum of photodynamic applications - Isci, Umit; Beyreis, Marlena; Tortik, Nicole; Topal, Sevinc Z.; Glueck, Michael; Ahsen, Vefa; Dumoulin, Fabienne (Elsevier, 2016)
Background: The biomedical photodynamic principle is based on the light-induced and photosensitizer-mediated killing of unwanted or harmful cells by overproduction of reactive oxygen species. Motivated by the success of photodynamic therapy (PDT) against several types of tumors, further applications of this approach are constantly identified which require the design and synthesis of novel photosensitizers with specifically tailored properties for a particular clinical application. Methods: Hydrophobic photosensitizers are currently gaining attention and hence a tetramethylsulfonyl Zn(II) phthalocyanine (2) was designed with respect to the desired photoproperties. The photodynamic potential of 2 was assessed by the determination of its photophysical and photochemical properties, and by a large range of biological tests including its phototoxicity against cancer cells and Gram(+) bacteria. Unsubstituted ZnPc was used as a reference compound for comparison purposes. Results: Phthalocyanine 2 has a better oxygen generation and is more photostable than ZnPc. 2 is a polyvalent and powerful hydrophobic photosensitizer with a wide spectrum of photodynamic applications against cancer (tested on A431 cells) and for Gram(+) PDI. Against Staphylococcus aureus, a maximum photokilling efficiency of more than 6 log10 steps was induced by a 5 mu M concentration of 2, outperforming the 3 log10 criterion for an antimicrobial effect (according to the recommendation of the American Society for Microbiology) by more than three orders of magnitude. Conclusions: Phthalocyanine 2 has attractive photophysical and -chemical characteristics. Initial evaluation of its application in anti-tumor PDT and PDI suggest potential for further pre-clinical and clinical development of this compound. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Photodynamic therapy; Photodynamic inactivation; Phthalocyanine; Singlet oxygen generation; In vitro